2020
DOI: 10.17159/2078-516x/2020/v32i1a7786
|View full text |Cite
|
Sign up to set email alerts
|

Strength and conditioning practices of franchise-level cricket trainers

Abstract: Background: The purpose of this investigation was to determine the strength and conditioning practices implemented by cricket trainers and coaches at an elite level. Methods: An online survey, adapted from previous strength and conditioning questionnaires, was sent to trainers currently working with the franchise cricket teams in South Africa. The survey consisted of four main sections including a general strength and conditioning, cricket- specific and injury prevention categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 15 publications
(30 reference statements)
1
16
0
Order By: Relevance
“…The response rate was similar to prior surveys in other professional sports (n = 20-43), [28][29][30][31][32][33] and higher than a survey conducted in professional cricket (n = 5). 23 Responses were received from seven countries where S&C coaches worked with professional international and club teams (see Figure 1). Professional cricket coaching certifications were held by 40% of S&C coaches, with the most reported being a Cricket South Africa (CSA) Level 2 (12%), English Cricket Board (ECB) Level 2 (9%), and CSA Level 3 (6%).…”
Section: Background Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…The response rate was similar to prior surveys in other professional sports (n = 20-43), [28][29][30][31][32][33] and higher than a survey conducted in professional cricket (n = 5). 23 Responses were received from seven countries where S&C coaches worked with professional international and club teams (see Figure 1). Professional cricket coaching certifications were held by 40% of S&C coaches, with the most reported being a Cricket South Africa (CSA) Level 2 (12%), English Cricket Board (ECB) Level 2 (9%), and CSA Level 3 (6%).…”
Section: Background Informationmentioning
confidence: 99%
“…3,[14][15][16][17][18][19][20][21][22] However, given the lack of research addressing the practices of S&C coaches in professional cricket, it is uncertain whether theoretical and research-informed guidelines are being adopted in actual practice, therefore warranting further investigation. 23 It has been shown that S&C coaches across different countries, sports and expertise levels, recommended using fundamental principles and exercises to provide a strong foundation for S&C programs. 24 Whereas, at the professional level this can be more complex, with a need to tailor programs to each players profile (e.g., injury history, goals, and position).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact composition of the greater body mass is open to speculation but the likely explanation is greater muscle mass. Previous work has shown correlations between strength and bowling release speed 42 and consequently large parts of the physical preparations strategy are targeted at increasing strength 46,47 . Other sports such as rugby have reported continued increases in body mass, and in some cases stature until athletes reach their early 20's 48 .…”
Section: Resultsmentioning
confidence: 99%